A rare presentation of rectal endometriosis - Mohanty, Arnab; Chatterjee, Debarghya (International Surgery Journal, 2021)
Endometriosis is the ectopic growth of viable endometrium outside the uterus, affecting approximately 7% women. It can occur in the absence of visible pelvic disease. Most common sites are gastrointestinal and urinary tract. Common sites of involvement are rectosigmoid (51%), appendix (15%), small bowel (14%), rectum (14%), cecum and colon (5%). Cyclical hematochezia is a definitive, but rare association of intestinal endometriosis. The diagnosis of colonic endometriosis is also difficult owing to the poor diagnostic yield of colonoscopy.